2011
DOI: 10.1590/s1415-790x2011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Variação temporal na prevalência do excesso de peso e obesidade em adultos: Brasil, 2006 a 2009

Abstract: Overweight and obesity are public health issues that affect an important part of the world population. This study aims at describing the trends in overweight and obesity prevalence rates from 2006 to 2009, by means of telephone surveys in 27 Brazilian cities, with a population aged 18 years or older. The body mass index (BMI) was calculated by the reported height and weight; overweight and obesity were considered as BMI ≥25 kg/m2 and ≥30 kg/m2, respectively. Temporal variation in overweight and obesity prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 8 publications
1
9
0
15
Order By: Relevance
“…Population-based surveys ratify the epidemic progress of overweight rates in the world and in Brazil, in the adult population [4][5][6][7] . Other studies show the association between socioeconomic and demographic indicators and the reported outcome 7,[8][9][10] . However, most studies analyzing the prevalence of overweight rates and associated factors used association analyses, by simple and multiple linear regressions 10 , as well as logistic and Poisson regressions [7][8][9] .…”
Section: Introductionmentioning
confidence: 96%
“…Population-based surveys ratify the epidemic progress of overweight rates in the world and in Brazil, in the adult population [4][5][6][7] . Other studies show the association between socioeconomic and demographic indicators and the reported outcome 7,[8][9][10] . However, most studies analyzing the prevalence of overweight rates and associated factors used association analyses, by simple and multiple linear regressions 10 , as well as logistic and Poisson regressions [7][8][9] .…”
Section: Introductionmentioning
confidence: 96%
“…Essas altas prevalências têm sido observadas nas capitais do Brasil, sendo que o sobrepeso variou de 41,7% em São Luís a 54,9% em Cuiabá e a obesidade de 13,2% a 22,4%, nas respectivas cidades 14 . Verificase, ainda, uma tendência de aumento da prevalência do excesso de peso entre mulheres com menor escolaridade (inferior a 12 anos de estudo) 15 e situadas nas faixas de renda mais baixas 16 . Com relação à obesidade abdominal, a maior prevalência em mulheres é inferior ao observado em estudos que avaliaram a relação da CC ao risco de desenvolvimento de doenças cardiovasculares, em São Paulo-SP 17 e Viçosa-MG 18 .…”
Section: Discussionunclassified
“…Evidências seccionais e longitudinais mostram padrão de associação inversa entre posição socioeconômica e obesidade, considerando-se principalmente escolaridade e o grupo de mulheres 1,2,3,5,6 . Escolaridade influencia a obesidade diretamente por meio de modos e estilos de vida relacionados à alimentação, atividade físi-ca e outras práticas de saúde 14 ; indiretamente, por meio da ocupação e renda.…”
Section: Discussionunclassified
“…No Brasil, mudanças socioeconômicas ocorridas nas últimas dé-cadas implicaram o aumento da disponibilidade de alimentos ultraprocessados e redução da atividade física 4 . Observou-se tendência crescente da prevalência e incidência de obesidade associada à baixa posição socioeconômica entre mulheres 5,6 .…”
Section: Introductionunclassified